Role of Chest Imaging in Clinically Suspected Extrapulmonary Tuberculosis Without any Chest Symptoms - Kumar, Sumit; Naik, Aishwarya; Rathi, Vinita; Tandon, Anupama (National Journal of Medical Research, 2025)
Background: Establishing a definitive diagnosis of EPTB can be very difficult in resource limited developing countries. Objective: To assess whether chest imaging (chest radiograph and/or CT chest) can play a significant role in the diagnosis of suspected EPTB. Methodology: Observational study was conducted in 120 patients of suspected EPTB who underwent radiography, sonography, or CT scan: or presented for review of any imaging studies done for EPTB. Chest Radiograph (CR) and CECT chest requested in these patients, who did not have pulmonary symptoms, were evaluated for tubercular infection. Results: The commonest EPTB encountered among 120 patients was abdominal tuberculosis in 44/120 patients (36.66%). Chest Radiograph suggested pulmonary TB in 48 out of 112 patients (42.85%) with suspected EPTB and 24 out of 32 patients (75%) who underwent CECT chest. In 56 out of 120 patients (46.66%), pulmonary TB was observed on combined chest imaging (CR + CECT Chest). The commonest CR finding in patients with suspected EPTB was lymphadenopathy in 32 patients (66.66%). The commonest lung abnormalities on CECT chest were tree-in-bud opacities in 20 out of 32 patients (62.5%), and matted, necrotic mediastinal lymph nodes were also seen in 20 patients (62.5%). Conclusion: Chest imaging can play a significant role in confirming diagnosis in 46% of suspected EPTB cases in whom available laboratory investigations are equivocal.